The effect of education level and economic growth on poverty in East Java - Septian, Aris Dwi; Soejoto, Ady; Pujiono, Pujiono (Technium Social Sciences Journal, 2021)
The effect of education level, economic growth on poverty in East Java. This study aims to know the effect of education level and economic growth partially and simultaneously on poverty in East Java 2014-2018 period. This study used a quantitative approach. The analysis method used is panel data analysis with fixed effect method approach. Data was collected using documentation techniques sourced from BPS and related goverment agencies. The study concluded that the level of education and economic growth negatively affect poverty levels partial and simultaneous.